Modifiable risk factors that influence the prevalence of diabetes mellitus II in the Quebrada “La Paja” community - Astudillo, Luis Á.; Chica, Karen A.; Sánchez, Génesis N.; Álvarez, Jimmy E.; Guzmán, María J. (Revista Gregoriana de Ciencias de la Salud, 2025)
Diabetes mellitus II is a common health problem associated with cultural and social changes, in addition to a sedentary lifestyle, lack of physical activity, and an unbalanced diet. The influence of lifestyles on the prevalence of diabetes mellitus II in the Quebrada “La Paja” community was analyzed. A cross-sectional, descriptive, observational research was conducted from April to September 2023. The most prevalent risk factors were coffee consumption, alcoholism, and smoking. The majority of the general population did not engage in physical activities. The influence of lifestyles and the prevalence of diabetes mellitus II was demonstrated. The findings indicated that unhealthy eating habits, sedentary lifestyle, and consumption of substances such as coffee, alcohol, and tobacco were modifiable risk factors that contribute to the increase in diabetes mellitus II.